Seizure as the clinical presentation of massive pulmonary embolism: Case report and literature review - Leong, Waiian; Zhang, Yueqi; Huang, Xinxiang; Luo, Zhendong; Wang, Yanli; Rainer, Timothy Hudson; Wai, Abraham K. C.; Huang, Yi (Frontiers in Medicine, 2022)
Massive pulmonary embolism (MPE) is a high-risk medical emergency. Seizures as the clinical presentation of MPE is extremely rare, and to our knowledge there have been no reports of successful percutaneous, catheter-based treatment of MPE presenting with new-onset seizures and cardiac arrest. We report a 64 year old woman who presented with an episode of seizure which lasted for 5 hours. The seizure occurred 4 times within 12 hours after arrival at hospital and at the end she sustained a cardiac arrest. There was no past history of seizure or cardiopulmonary disease. Bilateral MPE was detected by Computed Tomography Pulmonary Angiogram and she was treated successfully with percutaneous, catheter-directed anticoagulant therapy. Pulmonary embolism related seizures are more difficult to diagnose and have a higher mortality than seizures in general. MPE should be suspected in patients presenting with new-onset seizures and hemodynamic instability.